2018
DOI: 10.1093/humrep/dey115
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue – a symptom in endometriosis

Abstract: ClinicalTrials.gov, NCT 02511626.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
95
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(116 citation statements)
references
References 39 publications
9
95
0
2
Order By: Relevance
“…The contribution of pelvic pain (PP) to the psychosocial status and the quality of life (QoL) of women with endometriosis has been extensively addressed [6][7][8][9][10]. Additionally, chronic fatigue, i.e., the perception of physical tiredness and lack of energy distinct from sadness or weakness, is another endometriosis-related symptom, as recently identified in women with endometriosis [11]. However, the role of chronic fatigue on patients' lives has been poorly addressed, although a few qualitative studies have indicated that affected women ascribed social and work impairments to fatigue [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The contribution of pelvic pain (PP) to the psychosocial status and the quality of life (QoL) of women with endometriosis has been extensively addressed [6][7][8][9][10]. Additionally, chronic fatigue, i.e., the perception of physical tiredness and lack of energy distinct from sadness or weakness, is another endometriosis-related symptom, as recently identified in women with endometriosis [11]. However, the role of chronic fatigue on patients' lives has been poorly addressed, although a few qualitative studies have indicated that affected women ascribed social and work impairments to fatigue [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…There is no standard definition of "long-term" treatment for endometriosis, and dienogest 2 mg was approved on the basis of the clinical development program, which included studies lasting up to 15 months [24][25][26][27][28] . Although there have been few interventional studies since to investigate treatment durations beyond 15 months, supportive evidence for long-term dienogest treatment is available from a number of studies (Table 1) [1][2][3][4][5][6][7][8][9][10][11][12][13] . These studies show that administration of dienogest for up to 5 years is effective in preventing recurrence of disease and/or symptoms following surgery, and reducing endometriosis-associated pain 19,[29][30][31][32][33][34][35][36][37] .…”
Section: Efficacy With Long-term Dienogest Therapy For Endometriosismentioning
confidence: 99%
“…Pain is considered to be the defining symptom of endometriosis and can include dysmenorrhea, noncyclic pelvic pain, and/or dyspareunia 2,7 . Endometriosis can be both physically and emotionally debilitating, thereby significantly reducing a woman's quality of life [8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…1,3 Anxiety and depression are identified as recurrent psychological symptoms in women with endometriosis. [4][5][6][7] Such symptoms can compromise the daily life of endometriosis patients, affecting the family, social, professional, economic and personal areas, which justifies a multi professional intervention. 4,[7][8][9][10][11][12] The multi professional intervention can count on doctors specialized in pain, reproduction or gynecology, as well as psychologists, physiotherapists, acupuncturists, nutritionists, among others.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] Such symptoms can compromise the daily life of endometriosis patients, affecting the family, social, professional, economic and personal areas, which justifies a multi professional intervention. 4,[7][8][9][10][11][12] The multi professional intervention can count on doctors specialized in pain, reproduction or gynecology, as well as psychologists, physiotherapists, acupuncturists, nutritionists, among others. 6,7,13,14 Thus, the present study intends, through literature review, to identify the results obtained in individual or group psychotherapeutic intervention directed to the women with the diagnosis of endometriosis care.…”
Section: Introductionmentioning
confidence: 99%